The coupled bending-torsional dynamic behavior in the rotating machinery: modeling, simulation and experiment validation. (1st October 2022) - Li, Qihang; Chen, Can; Gao, Shuai; Ren, Yinglin; Wang, Weimin
Graphical abstract: Abstract: The nonlinear coupling between bending and torsional vibrations would greatly affect the dynamic behavior of the rotor system. Different from the traditional way, in this paper the unbalance mass that causes the internal and external couplings is treated as an independent nonlinear element when establishing a finite element model of the coupled bending-torsional (CBT) rotor system with six degrees of freedom for each node. To improve the efficiency of transient numerical simulation, a general algorithm named with linear and nonlinear nodes separation method is proposed, which decreases the dimension of nonlinear iteration matrix, resulting in a great calculation efficiency of solving transient vibration responses of the high-dimension nonlinear motion equation. With the presented nonlinear CBT model, simulations for steady and transient torsional excitation processes are carried out, resulting that the torsional excitation would generate sideband frequency components in the spectra of lateral vibrations and vice versa, and the effect of gravity is considerable and non-negligible in CBT modeling. Additionally, results of experiments with two different scales of setups, a laboratory test-rig and an industrial centrifugal compressor platform, are well agreed with the numerical ones. The investigation provides a complete modeling and high efficient solution method not only for CBT rotordynamic problems, but also for other problems with nonlinear forces.